The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1016/j.gloenvcha.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Policy invention and entrepreneurship: Bankrolling the burying of carbon in the EU

Abstract: This article presents the case of a policy invention where various kinds of entrepreneurship and a window of opportunity played important roles. In 2008 the EU adopted a new Carbon Capture and Storage (CCS) policy with an inventive funding instrument at its core: the NER 300 fund, based on revenues from the auctioning of emissions trading allowances. Thus far, the literature on policy entrepreneurs has focused more on success factors that enable particular persons to be especially influential than on the defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…We have already noted how such studies tend to gloss over the subtle but important differences between and within individual policies; analysts are also becoming more aware of their insensitivity to slow processes of refinement as policies diffuse and take root in particular jurisdictions 54 . Case study analyses have shown that groups advocating particular policy instruments (such as emissions trading 11 ) drive these processes, often in collaboration with policy entrepreneurs 55,56 .…”
Section: Originsmentioning
confidence: 99%
“…We have already noted how such studies tend to gloss over the subtle but important differences between and within individual policies; analysts are also becoming more aware of their insensitivity to slow processes of refinement as policies diffuse and take root in particular jurisdictions 54 . Case study analyses have shown that groups advocating particular policy instruments (such as emissions trading 11 ) drive these processes, often in collaboration with policy entrepreneurs 55,56 .…”
Section: Originsmentioning
confidence: 99%
“…Following Knaggård (, p. 450), we term the role that an entrepreneur plays in this stream as the problem broker. This could involve generally creating awareness about the problem (Boasson & Wettestad, ; Kalafatis, Grace, & Gibbons, ; Knaggård, ; Meijerink & Huitema, ); capitalizing on specific focusing events to draw attention (Mallett & Cherniak, ); altering problem perception using performance indicators and standards (Maor, ); altering societal norms through legal, moral, or political authority (Maor, ); linking issues (Brouwer & Huitema, ; Mallett & Cherniak, ) or brokering knowledge (Knaggård, ). The problem broker relies on discursive or narrative reframing (Lovell, ; Meijerink & Huitema, ), institutional delegitimization (Goldfinch & Hart, ), or rhetorical persuasion (Brouwer & Huitema, ) to make policy makers accept the problem frame.…”
Section: Theoretical Framework: Disaggregating Entrepreneurship Withimentioning
confidence: 99%
“…Following Knaggård (2015, p. 450), we term the role that an entrepreneur plays in this stream as the problem broker. This could involve generally creating awareness about the problem (Boasson & Wettestad, 2014;Kalafatis, Grace, & Gibbons, 2015;Knaggård, 2016;Meijerink & Huitema, 2010); capitalizing on specific focusing events to draw attention (Mallett & Cherniak, 2018); altering problem perception using performance indicators and standards ; altering societal norms through legal, moral, or political authority ; linking issues 1 Although elite interviews are useful for uncovering entrepreneurial activity , they can also lead to bias as "success may well be attributed to those adept at playing the media" (Meijerink & Huitema, 2010, p. 24). 2 For news reports, we used the Lexis Academic database to obtain and parse over 1000 news reports specifically on JGY and, more broadly, the electricity sector in Gujarat.…”
Section: Problem Brokermentioning
confidence: 99%
See 1 more Smart Citation
“…We find that the literature on policy entrepreneurship pays limited explicit analytical or conceptual attention to cross-boundary strategies. An exception is the notion of "venue shopping", "venue shifting" or "venue manipulation" (Boasson and Wettestad 2014, Boekhorst et al 2010, Carter and Jacobs 2014, Mukhtarov et al 2013, Pralle 2006, an activity related to shifting the decisionmaking authority to a different arena, which is discussed not only in the policy entrepreneurship literature but also more broadly in relation to the policy process literature, most importantly punctuated equilibrium theory (Baumgartner andJones 2010, Pralle 2003a). The increasing number of articles addressing boundary-crossing in our sample might well be aligned to the increasing attention for crosscutting policy issues.…”
Section: Discussionmentioning
confidence: 99%